MICROSTRUCTURE AND ELECTRICAL PROPERTIES OF CACO3-DOPED ZNO– (BI2O3, SB2O3) BASED VARISTOR CERAMICS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this study, varistors based on ZnO were developed according to this composition, where the varistors based on 0.5 % Bi2O3 / 0.5 % Sb2O3 / 99 % ZnO doped with 1 % molar, 2 % molar, and 4 % molar CaCO3 all samples are prepared by the conventional ceramic method in a programmable oven, the samples were sintered at a fixed temperature of 1000 °C in the air for two hours. To see the influence of CaCO3, the additive, the microstructure, and the densification behavior have been taken into consideration, in addition to this, the electrical properties of the ZnO varistor ceramics have been studied in detail. The average grain size is measured and determined through scanning electron microscopy (SEM) equipped with an energy-dispersive X-ray analyzer (EDX). The crystallinity of the samples was determined by X-ray diffraction. According to all these measurements, it was seen that the increase in the quantity of CaCO3 slightly decreased the relative density of the sintered pellets in the range of 98.2 to 97.2 %, and the average size of the grains increased slightly in the range of 1.75 µm to 2.89 µm. The union of CaCO3 markedly increased the breakdown field from 83 to more than 1000 V/mm. The sample with 4 mol % CaCO3 had the highest nonlinear coefficient, and on the other hand, the sample with no amount of CaCO3 had the lowest nonlinear coefficient. Moreover, the relative density and the leakage current (IL) decreased with the increase in the amount of CaCO3.
Keywords: Varistor; CaCO3 doped- ZnO; Bi2O3; Sb2O3; Microstructure; Nonlinear coefficient